FRACTAL ANALYSIS AND FORECASTING OF BUDGETING EFFICIENCY IN UKRAINE UND ERCONDITIONS OF TRANSFORMATIONAL CHANGE - Квасній, Марія; Тимергазіна , Вероніка (Socio-economic relations in the digital society, 2019)
The article analyzes the revenue and expenditure part of the budget of Ukraine, assesses their dynamicsbased on the use of basic and chain indexes, and it is established that the dynamics of the budget is nonlinear with a nonsmooth character — alternatively, it increases, then decreases. To analyze the efficiency of budgeting, the income expense ratio has been calculated and imbalances have been identified. The author's concept of forecasting of budgeting efficiency in Ukraine is proposed on the basis of fractal analysis and determination of the type of dynamics, the method of organization of the process and integration of the totality of mathematical methods of forecasting with the help of moving average, exponentially smoothed simple average, growth rates taking into account seasonality and Hurwitz's criterion. Projections are made taking into account instability of fi lling and distribution of the budget of Ukraine in the conditions of transformation changes.
Keywords: budget of Ukraine; coefficient of budgeting efficiency; fractal analysis; integration of methods; sliding average; growth rate; Hurwitz criterion